The Role of External Actors in Supporting Social and Political Action towards Empowerment and Accountability with a Focus on Fragile, Conflict- and Violence-Affected Settings - Christie, Angela; Burge, Richard (IDS and ITAD, 2017)
This paper explores the role and experience of external actors, particularly donors, in supporting social and political action in fragile, conflict and violence affected settings. Evidence is distilled from a wide range of synthesised sources to generate relevant findings and questions in relation to what we know and what we don’t. Included among the source material is a 2016 macro-evaluation of DFID’s empowerment and accountability (E&A) programmes which examined over 50 DFID funded projects. Themes which emerge relate to: how external actors need to think about the context and work politically; who are the most appropriate social and political actors to support in E&A; whether a direct or indirect approach to support for E&A achieves more tangible outcomes; whether external actors should move beyond short-term tools and tactics focused on one-sided engagement; and whether programmes should be designed around more strategic, multi-faceted interventions. The paper concludes with identifying a number of gaps in the evidence which are translated into a range of questions which could potentially inform the Action for Empowerment and Accountability (A4EA) research programme.

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Pyoe Pin, Myanmar - Christie, Angela; Green, Duncan (Itad, Oxfam and IDS, 2018)
This paper examines adaptive approaches in aid programming in a fragile, conflict and violence-affected setting (FCVAS), namely Myanmar. A combination of desk review and field research has been used to examine some of the assertions around the ‘adaptive management’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blue-print and linear project plans. This paper explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for promoting empowerment and accountability in such ‘messy places’. This case study focuses on Pyoe Pin (‘Young Shoots’), a DFID-funded, British Council managed governance programme, which has been running since 2007.
Keywords: A4EA; Adaptive Development; Economy; Fishery

The Case for an Adaptive Approach to Empowerment and Accountability Programming in Fragile Settings: Synthesis report - Christie, Angela; Green, Duncan (Itad, Oxfam and IDS, 2019)
Fragile, conflict and violence-affected settings (FCVAS) are messy and ambiguous contexts in which to plan and implement development initiatives. To work there, external actors are increasingly adopting an adaptive approach to empowerment and accountability (E&A) programming, whatever the setting. This means using a compass rather than map, where real-time political economy analysis (PEA) in relation to context and programme monitoring and evidence-informed learning in relation to intervention are used in combination and in shorter-than-usual planning cycles to maintain and adapt strategic direction. This paper brings together three case studies of large Department for International Development (DFID) governance projects in Myanmar, Nigeria and Tanzania.
Keywords: A4EA; Adaptive Development; Economy; Fishery